Chronic Granulocytic Leukaemia: Multiple-drug Chemotherapy for Acute Transformation. Issue 5923 (13th July 1974) - Spiers, A. D. S.; Costello, Christine; Catovsky, D.; Galton, D. A. G.; Goldman, J. M.
Abstract : The response to 60 trials of therapy in 50 patients with chronic granulocytic leukaemia (C.G.L.) in acute transformation is reported. None of the 13 patients who received single-agent chemotherapy had a satisfactory response. The use of two drugs in combination produced only one satisfactory response in 30 patients. Various types of multiple-drug treatments in eight patients achieved one good response which lasted four months. In contrast when nine patients with rapidly progressive acute transformation of C.G.L. received a regimen—TRAMPCO(L)—incorporating seven or eight drugs (thioguanine, daunorubicin, cytarabine, methotrexate, prednisolone, cyclophosphamide, and vincristine, with or without L-asparaginase colaspase) five improved significantly. Four patients had a good clinical and haematological response with survival for over three, eight, over 12, and 14 and a half months; and one patient had a partial response. Toxicity was not extreme and maintenance therapy with the same regimen was given on an outpatient basis. TRAMPCO(L) seems superior to previously reported regimens and should be considered for rapidly progressive transformation of C.G.L. especially when simpler treatments have failed.